Južnoslovanski jeziki v slovenskem izobraževanju - Balažic Bulc, Tatjana (Slavistična revija, 2018)
The issue of foreign languages is one of the current issue in the field of language education policy. It is evident from the curricula and other accompanying documents, that Slovene language policy follows the principles of the Council of Europe on the plurilingualism and importance of minority and neighbouring languages. The range of foreign languages offered in schools is in accordance with the guidelines of Slovene language education policy, however, the question is how these subjects are implemented in practise. In this paper, we focus on the status of South Slavic languages in Slovene education system, as well as their realisation in praxis.
Keywords: hrvaščina; izobraževalna politika; jezikovna politika; južnoslovanski jeziki; raznojezičnost; tuji jezik